Methods and Factors Influencing In Vitro Propagation Efficiency of Ornamental Tuberose (Polianthes Species): A Systematic Review of Recent Developments and Future Prospects - Mukesh Kumar; Ujjwal Sirohi; Sunil Malik; Satendra Kumar; Gaurav Kumar Ahirwar; Veena Chaudhary; Manoj Kumar Yadav; Jitender Singh; Arvind Kumar; Virendra Pal; Satya Prakash (Horticulturae, 2022)
In vitro propagation greatly boosts the propagation rate and allows for the development of disease-free plants. In the near future, new in vitro propagation methods could make it easier to produce plants true to type on a wide scale and to use genetic engineering to improve genotypes. Various factors, such as genotype, explant type, size of explants, position of explants on the medium, plant growth regulators and certain additives, incubation conditions, and sub-culturing time, all have a significant impact on the in vitro generation of plantlets and bulblets. However, numerous studies on in vitro propagation have been published, but there is very little information on the parameters that affect the in vitro efficiency of tuberose. The efficiency of bulblet production in ornamental tuberose as well as different physical, nutritional, and hormonal aspects are discussed in this manuscript along with several in vitro propagation strategies (direct, indirect, and somatic embryogenesis). Future research opportunities and the use of creative ways to improve ornamental tuberose are also highlighted. As a whole, this review provides an insight toward a complete protocol for in vitro propagation in tuberose, highlighting the factors influencing the in vitro efficiency and future strategies for improving in vitro plantlets and bulblets in ornamental tuberose.